Dr. Felipe Reynaldo Soto Padrón: dentist and health care worker - Leinen de la Caridad Cartaya Benítez; Rolando Mirot Delgado; Ivis Páez Cartaya (Universidad de Ciencias Médicas de La Habana, 2023)
Dr. Felipe Reynaldo Soto Padrón was noted for his participation in revolutionary activities, international collaboration, and the formation of human resources in Dentistry at the intermediate level which included the development of Dental Assistant courses in Boyeros municipality after the triumph of the Cuban Revolution. A historical investigation was carried out to gather biographical data; his work record of the Municipal Combatants Association of Bejucal was consulted as documentary source, along with the documentation provided by family and friends, then the gathered information was organized chronologically. The objective of the present biography is to disclose the main aspects of his professional career. He became a precursor of the Public Health Care and Health Administration in Cuba, and he was very interested in the investigation of topics such as the prevention of dental caries and dental care for pregnant women.